A NEW OS ARCHITECTURE FOR IOT - Jean Y. Astier; Igor Y. Zhukov; Oleg N. Murashov; Alexey P. Bardin (Безопасность информационных технологий, 2018)
Current computer operating systems architectures are not well suited for the coming world of connected objects, known as the Internet of Things (IoT) for multiple reasons: poor communication performances in both point-to-point and broadcast cases, poor operational reliability and network security, excessive requirements both in terms of processor power and memory size leading to excessive electrical power consumption. We introduce a new computer operating system architecture well adapted to IoT, from the most modest to the most complex, and more generally able to significantly raise the input/output capacities of any communicating computer. This architecture rests on the principles of the Von Neumann hardware model, and is composed of two types of asymmetric distributed containers, which communicate by message passing. We describe the sub-systems of both of these types of containers, where each sub-system has its own scheduler, and a dedicated execution level.